Ethical Frameworks and Global Health: A Narrative Review of the "Leave No One Behind" Principle - Daniela Oehring PhD; Poorna Gunasekera MSc (SAGE Publishing, 2024)
The "Leave No One Behind" (LNOB) principle, a fundamental commitment of the United Nations' Sustainable Development Goals, emphasizes the urgent need to address and reduce global health inequalities. As global health initiatives strive to uphold this principle, they face significant ethical challenges in balancing equity, resource allocation, and diverse health priorities. This narrative review critically examines these ethical dilemmas and their implications for translating LNOB into actionable global health strategies. A comprehensive literature search was conducted using PubMed, Scopus, Web of Science, and Semantic Scholar, covering publications from January 1990 to April 2024. The review included peer-reviewed articles, gray literature, and official reports that addressed the ethical dimensions of LNOB in global health contexts. A thematic analysis was employed to identify and synthesize recurring ethical issues, dilemmas, and proposed solutions. The thematic analysis identified 4 primary ethical tensions that complicate the operationalization of LNOB: (1) Universalism versus Targeting, where the challenge lies in balancing broad health improvements with targeted interventions for the most disadvantaged; (2) Resource Scarcity versus Equity; highlighting the ethical conflicts between maximizing efficiency and ensuring fairness; (3) Top-down versus Bottom-up Approaches, reflecting the tension between externally driven initiatives and local community needs; and (4) Short-term versus Long-term Sustainability, addressing the balance between immediate health interventions and sustainable systemic changes. To navigate these ethical challenges effectively, global health strategies must adopt a nuanced, context-sensitive approach incorporating structured decision-making processes and authentic community participation. The review advocates for systemic reforms that address the root causes of health disparities, promote equitable collaboration between health practitioners and marginalized communities, and align global health interventions with ethical imperatives. Such an approach is essential to truly operationalize the LNOB principle and foster sustainable health equity.